La laïcité française - Patrick Michel (Les Cahiers ALHIM)
Although ‘laïcité’ has had an influence over France’s secularization, it has also contributed to slowing down its effects by bringing out the conditions leading to the spreadout of a ‘republican religion of substitution’. And yet, if ‘laïcité’ and religion both find their root in the same attestation of a central reference, a blow to the credibility of any kind of centrality results as much in a disaffection with ‘laïcité’ as it does with religion. The high visibility of the pluralism induced by the somewhat overwhelming presence of Islam is likely to bring back to life the question of ‘laïcité’. The call for a ‘positive laïcité’ made by President Nicolas Sarkozy therefore corresponds to the political vision of a religion thought out as a resource necessary both to the build up of social cohesion as well as that of law enforcement. This view plays a part in the confusion between ‘laïcité’ and secularization and in a suspicion which surrounds society and autonomy. It is also constructed on a deep misunderstanding of democracy’s capacity for producing value. It is a sign that the State is weak, only able to conjure up religion in order to re-enchant the political field, to try to handle the turmoil in which it finds itself because of the current movement’s tendency to speed up.